The Sexual Dimorphism in Rectum and Protein Digestion Pathway Influence Sex Pheromone Synthesis in Male Bactrocera Dorsalis - Jingxiang Chen; Yanling Jiang; Zijie Gao; Jiawang Dai; Chunsheng Jia; Yongyue Lu; Daifeng Cheng (Advanced Science)
Abstract Sexual dimorphism is a crucial aspect of mating and reproduction in many animals, yet the molecular mechanisms remain unclear. In Bactrocera dorsalis, sex pheromones trimethylpyrazine (TMP) and tetramethylpyrazine (TTMP) are specifically synthesized by Bacillus strains in the male rectum. In the female rectum, Bacillus strains are found, but TMP and TTMP are not, indicating sexually dimorphic differences in sex pheromone synthesis. Our anatomical observations and precursor measurements revealed significant differences in rectal structure and ammonium levels between sexes.  In vitro and in vivo experiments reveal that ammonium is vital for sex pheromone synthesis in rectal Bacillus strains. Comparative transcriptome analysis identified ammonium‐producing genes (carboxypeptidase B and peptide transporter) in the protein digestion pathway that show much higher expression in the male rectum than in the female rectum. Knocking down the expression of either carboxypeptidase B (or inhibiting enzyme activity) or peptide transporter decreases rectal ammonium levels significantly, resulting in the failure of sex pheromone synthesis in the male rectum. This study provides insights into the presence of sexual dimorphism in internal organs and their functionalities in male‐specific sex pheromone synthesis and has significant implications for understanding the molecular mechanisms underlying sex pheromone synthesis by symbionts in insects.